Assessment of neuroprotective potential of Tualang honey in alzheimer model of rat - Saxena, Anil Kumar; Phyu P, Hnin; A.Talib, Norlelawati; Al-Ani, Imad Matloub Dally (2014)
Reduction in cerebral blood flow (CBF) due to aging has been associated with neurodegenerative disorders including Alzheimer’s disease and dementia. Experimentally, a condition of chronic cerebral hypoperfusion due to reduced CBF can be induced by permanent bilateral occlusion of common carotid arteries (2-vessel occlusion, 2VO) in rats. Honey is a natural product that has been widely used since long time as a nutrient, for its therapeutic effects in traditional medicine, and recently as an antioxidant. Since oxidative stress leading to neuroinflammation, resulting in neuronal apoptosis and death, is one of the mechanisms which is thought to play a significant role in chronic degenerative neurological disorders, the present study was planned to assess the neuroprotective role of Honey in chronic cerebral hypoperfusion-induced neurodegeneration. After acclimatization, thirty Sprague Dawley rats weighing 200-250 g were equally divided into three groups. Group A – sham control, Group B – 2VO, and Group C – 2VO-H (treated daily with Honey (1.2 g/kg freshly diluted with distilled water, orally by 30 gavage every morning following 2VO). At 10th week, all the rats were euthanized and the hippocampi were isolated. Viable neuronal cell were count in the hippocampal CA-1 region. The results showed damaged, distorted, irregular cells with shrunken cytoplasm and dark pykonotic nuclei in 2VO rats as compared to sham control (p<0.001). Treatment of rats with honey restored the hippocampal cells to their normal structure and revealed the reduced loss of neurons in 2VO+H rats as compared to untreated 2VO rats (p<0.001). This study shows that Malaysian tualang honey might have therapeutic potential for the treatment of chronic cerebral hypoperfusion related neurodegenerative disorders including Alzheimer’s disease.